Physiological responses to 1000-m ergometer time-trial performance in outrigger canoeing - Kerr, R.; Spinks, W.; Leicht, A.; Sinclair, W.; Woodside, L. (Journal of Sports Sciences, 2008)
Graded exercise tests are commonly used to assess peak physiological capacities of athletes. However, unlike time trials, these tests do not provide performance information. The aim of this study was to examine the peak physiological responses of female outrigger canoeists to a 1000-m ergometer time trial and compare the time-trial performance to two graded exercise tests performed at increments of 7.5 W each minute and 15 W each two minutes respectively. 17 trained female outrigger canoeists completed the time trial on an outrigger canoe ergometer with heart rate (HR), stroke rate, power output, and oxygen consumption ([Vdot]O2) determined every 15 s. The mean (± s) time-trial time was 359 ± 33 s, with a mean power output of 65 ± 16 W and mean stroke rate of 56 ± 4 strokes · min-1. Mean values for peak [Vdot]O2, peak heart rate, and mean heart rate were 3.17 ± 0.67 litres · min-1, 177 ± 11 beats · min-1, and 164 ± 12 beats · min-1 respectively. Compared with the graded exercise tests, the time-trial elicited similar values for peak heart rate, peak power output, peak blood lactate concentration, and peak [Vdot]O2. As a time trial is sport-specific and can simultaneously quantify sprint performance and peak physiological responses in outrigger canoeing, it is suggested that a time trial be used by coaches for crew selection as it doubles as a reliable performance measure and a protocol for monitoring peak aerobic capacity of female outrigger canoeists.